Entry, survival and growth in a new market: The case of the encryption software industry - Marco S. Giarratana (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2002)
This paper analyzes the birth of the Encryption Software Industry (ESI), a new market niche in the software industry. This work will report the main facts of entry and exit process, focusing on firm post-entry performance, on the different phases of competition during the industry evolution, and on the strategic actions of main actors. ESI represents an interesting case study. It originated during the mid-1970s when market opportunities, arising from the military sector, spurred established electronic firms like IBM and Motorola to accumulate knowledge in encryption software technology.Empirical evidence shows that years later, despite their early entry into the technological race, the large firms were slow or late to enter into the civilian market, leaving new comers the opportunity to dominate the product market for this fast growing demand. In order to analyze ESI development, we have collected a wide series of data on introduction of products, patents granted by the US Patent Office, worldwide alliances in the sector and some biographical data about founders of startups and their executives. This paper highlights two different topics that emerge from the history of the ESI.First, the study of startups dynamics and factors spurring startup growth, where size is an important determinant of firm ability to survive in young and competitive industries. Second, the rationality behind the motivations of incumbent behavior arises an interesting puzzle to decipher: was the adoption of a wait-and-see strategy a rational and optimal decision by incumbents, or maybe, were large firms affected by problems of organization inertia and strategic myopia?
Keywords: 330; Unternehmensgründung; Markteintritt; Branchenentwicklung; Softwareindustrie; USA; Marktaustritt